2014
DOI: 10.1007/s10815-014-0211-6
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of INS VNTR polymorphism with polycystic ovary syndrome: a meta-analysis

Abstract: Purpose An association between the INS VNTR polymorphisms and polycystic ovary syndrome (PCOS) susceptibility has been reported in previous studies, but the results were inconsistent. This study was conducted to explore this association using meta-analysis. Methods PubMed, Embase, and China National Knowledge Infrastructure (CNKI) were searched according to predefined criteria for all relevant studies published up to August 2013. Four genetic models, together with odds ratios (ORs) and 95 % confidence interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Nevertheless, due to the impact of insulin resistance and hyperinsulinemia on anovulation, there may be an association between insulin-related genes and ovulation. While in a meta-analysis study, no association between INS VNTR gene and PCOS was observed [ 63 ], INS VNTR class III allele is correlated with increased HOMA-IR and BMI in Kashmiri women with PCOS [ 64 ]. A set of previous studies have shown that the variable number of tandem repeat of INS gene is not likely to be dependent on PCOS in different populations ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, due to the impact of insulin resistance and hyperinsulinemia on anovulation, there may be an association between insulin-related genes and ovulation. While in a meta-analysis study, no association between INS VNTR gene and PCOS was observed [ 63 ], INS VNTR class III allele is correlated with increased HOMA-IR and BMI in Kashmiri women with PCOS [ 64 ]. A set of previous studies have shown that the variable number of tandem repeat of INS gene is not likely to be dependent on PCOS in different populations ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%